Trends in diabetes incidence from 1992 to 2015 and projections for 2024: A Portuguese General Practitioner's Network study. Issue 5 (October 2016) - de Sousa-Uva, Mafalda; Antunes, L.; Nunes, B.; Rodrigues, A.P.; Simões, J.A.; Ribeiro, R.T.; Boavida, J.M.; Matias-Dias, C.
Highlights: Diabetes incidence increased 4.29% per year, since 1992 to 2015 in Portugal. The incidence rate projected for 2022–2024 was 972.77/10 5 inhabitants. This represents the first study in Portugal about this issue. This study could support public health goals aimed to reduce diabetes impact. Abstract: Background: Diabetes is known as a major cause of morbidity and mortality worldwide. Portugal is known as the European country with the highest prevalence of this disease. While diabetes prevalence data is updated annually in Portugal, the General Practitioner's (GP) Sentinel Network represents the only data source on diabetes incidence. This study describes the trends in Diabetes incidence, between 1992 and 2015, and estimate projections for the future incidence rates in Portugal until 2024. Methods: An ecological time-series study was conducted using data from GP Sentinel Network between 1992 and 2015. Family doctors reported all new cases of Diabetes in their patients' lists. Annual trends were estimated through Poisson regression models as well as the future incidence rates (until 2024), sex and age group stratified. Incidence rate projections were adjusted to the distribution of the resident Portuguese population given Statistics Portugal projections. Results: The average increase in Diabetes incidence rate was in total 4.29% (CI95% 3.80–4.80) per year under study. Until 1998–2000, the annual incidence rate was higher in women, and from 1998–2000 to 2013–2015 turn out to be higher in men. The incidence rate projected for 2022–2024 was 972.77/10 5 inhabitants in total, and 846.74/10 5 and 1114.42/10 5, respectively, in women and men. Conclusions: This is the first study in Portugal to estimate diabetes incidence rate projections. The disturbing reported projections seem realistic if things continue as in the past. Actually, effective public health policies will need to be undertaken to minimize this alarming future scenario.